A systematic review of activities of daily living measures for children and adolescents with cerebral palsy. (13th August 2013) - James, Sarah; Ziviani, Jenny; Boyd, Roslyn
<x xml:space="preserve">Abstract</x> Aim This study aimed to systematically review the psychometric properties and clinical utility of measures of activities of daily living (ADL) for children with cerebral palsy (CP) aged 5 to 18 years. Method Five electronic databases were searched to identify available ADL measures with published psychometric data for school‐aged children with CP. Measures were included if at least 60% of the items addressed ADL in the full assessment or in an independent domain. A modified CanChild Outcome Rating Form was used to report the validity, reliability, responsiveness, and clinical utility of the measures. Results Twenty‐six measures were identified and eight met inclusion criteria. The Pediatric Evaluation of Disability Inventory (PEDI) had the strongest psychometric properties but was limited by its age range. The Assessment of Motor and Process Skills (AMPS) was the most comprehensive evaluation of underlying motor and cognitive abilities yet further psychometric testing is required for children with CP. Interpretation The PEDI should be used to measure ADL capability in elementary school aged children. The AMPS is the best measure to evaluate ADL performance or capacity and is suitable for all ages. Future research should examine the reliability of the AMPS to determine its stability in children and adolescents with CP.